2019
DOI: 10.4314/njp.v45i3.2
|View full text |Cite
|
Sign up to set email alerts
|

Pre-presentation management, metabolic state and outcome of children admitted for diarrhoea disease in Calabar, Nigeria

Abstract: Background: Much of the activities for the prevention and management of diarrhoea should occur or be initiated at home. In addition, management is guided by clinical and metabolic state. This work was designed to examine some prehospital management practices and the metabolic state of children with diarrhoea in Calabar, Nigeria.Methodology: Prospective study of the pre-presentation management, clinical and metabolic states of children with diarrhoea presenting at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…Our study found that the most common home remedy offered by caregivers was mainly ORS (79.4%) which is in keeping with the 47-72.3% rate within the country, [25,26] and the most common source of drinking water was sachet/bottled water (47.8%). This finding is reassuring and in line with the WHO/UNICEF [1] recommendation.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Our study found that the most common home remedy offered by caregivers was mainly ORS (79.4%) which is in keeping with the 47-72.3% rate within the country, [25,26] and the most common source of drinking water was sachet/bottled water (47.8%). This finding is reassuring and in line with the WHO/UNICEF [1] recommendation.…”
Section: Discussionsupporting
confidence: 83%
“…Our findings were lower than the reported prevalence of acidosis in Nigeria. [25,26] In contrast, hypernatremia (37.9%) was the most common electrolyte derangement as reported by researchers from Tanzania. [32] Our study revealed that none of the babies managed for diarrhea had hypoglycemia.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…18 In contrast however, it was lower than the prevalence of 44.5% and 44.3% described by Dhyani et al in India and Okposio et al in Benin, Nigeria respectively. 13,28 A lower prevalence of 13.64% was however documented in Calabar, South-south Nigeria by Uka et al 30 These differences may possibly be due to the differences in clinical characteristics of the subjects, and the study population. The preponderance of hypokalaemia in patients with SAM and in the intensive care unit has been documented.…”
Section: Discussionmentioning
confidence: 82%